2017
DOI: 10.1007/s00429-017-1519-7
|View full text |Cite
|
Sign up to set email alerts
|

Brain structural concomitants of resting state heart rate variability in the young and old: evidence from two independent samples

Abstract: Previous research has shown associations between brain structure and resting state high-frequency heart rate variability (HF-HRV). Age affects both brain structure and HF-HRV. Therefore we sought to examine the relationship between brain structure and HF-HRV as a function of age. Data from two independent studies were used for the present analysis. Study 1 included 19 older adults (10 males, age range 62–78 years) and 19 younger adults (12 males, age range 19–37). Study 2 included 23 older adults (12 males; ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

8
87
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 71 publications
(95 citation statements)
references
References 52 publications
8
87
0
Order By: Relevance
“…A negative correlation was reported between resting HRV (indexed by high‐frequency HRV) and the left isthmus cingulate cortex. These findings were partly replicated by a later report (Yoo et al, ), drawing on a total of n = 85 (37 female) adult participants from two independent samples comprising two age groups each (18–37 years and 62–78 years). In a meta‐analysis across findings from both samples, independent of age, the report found a correlation between resting state HRV and cortical thickness of the caudal and rostral ACC of the left hemisphere, the left lateral orbitofrontal cortex (OFC), the left and right caudal MFG, the left and right SFG, the left and right insula, the left and right pars opercularis, the right pars triangularis, and the right pars orbitalis.…”
Section: Introductionmentioning
confidence: 57%
See 3 more Smart Citations
“…A negative correlation was reported between resting HRV (indexed by high‐frequency HRV) and the left isthmus cingulate cortex. These findings were partly replicated by a later report (Yoo et al, ), drawing on a total of n = 85 (37 female) adult participants from two independent samples comprising two age groups each (18–37 years and 62–78 years). In a meta‐analysis across findings from both samples, independent of age, the report found a correlation between resting state HRV and cortical thickness of the caudal and rostral ACC of the left hemisphere, the left lateral orbitofrontal cortex (OFC), the left and right caudal MFG, the left and right SFG, the left and right insula, the left and right pars opercularis, the right pars triangularis, and the right pars orbitalis.…”
Section: Introductionmentioning
confidence: 57%
“…In a meta‐analysis across findings from both samples, independent of age, the report found a correlation between resting state HRV and cortical thickness of the caudal and rostral ACC of the left hemisphere, the left lateral orbitofrontal cortex (OFC), the left and right caudal MFG, the left and right SFG, the left and right insula, the left and right pars opercularis, the right pars triangularis, and the right pars orbitalis. Results indicated that greater cortical thickness of the OFC was associated with greater HRV regardless of age, whereas the association with the ACC was only evident among younger adults (Yoo et al, ). Importantly, with the exception of a significant correlation between cortical thickness of the left caudal ACC and mean heart rate (HR) in one subsample, the study illustrated that the association between cortical thickness and autonomic function was unique to HRV—not HR (Yoo et al, ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…For instance, greater baseline RMSSD is associated with greater functional connectivity between amygdala and medial prefrontal cortex (Sakaki et al, 2016). Furthermore, across individuals, greater structural thickness in the anterior cingulate and prefrontal regions was associated with greater HF-HRV/RMSSD across several samples and among both younger and older adults (Winkelmann et al, 2016; Yoo et al, In preparation). These findings provide important insights into the cortical control of HF-HRV.…”
Section: Introductionmentioning
confidence: 91%